Maker-centred learning approach to craft stem education in primary schools: a systematic literature review - Balakrisnan, Vijaya; Kamarudin, Nurzatulshima; Hassan, Aminuddin; Ma'rof, Aini Marina (Akademi Sains Malaysia, 2023)
The implementation of STEM (Science, Technology, Engineering and Mathematics) in primary schools is a new avenue for researchers and educators. Several studies have reported the needs, barriers and threats and tested instructional methods in general. In Malaysian primary schools, it is still a work in progress and a great challenge to deal with existing issues in teaching and learning primary science. Hence, education futurists have redirected science learning by commercialising the student-centred learning model of makerspace with STEM elements, which combines high-tech tools and materials. Besides, in the Scopus database, the number of researches on the STEM education infused maker concept shows notable figures. Therefore, this study presents a systematic literature review on implementations of the STEM-Maker concept in primary schools for in-depth understanding and application. A checklist of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) is referred to and applied. Eight STEM-Maker concept implementations and six STEM-Maker concept practices were identified from 13 shortlisted articles. The citation, purpose and primary results of each shortlisted study are also discussed in this paper. To establish a solid foundation in science with transversal competencies in primary education, the bridging concept of the Maker with STEM education would be a tremendous opportunity to instil future skills under one roof.